Implementasi Kebijakan Grup Policy Untuk Mitigasi Risiko Keamanan Pada Server di PT XYZ - Rifqi Muhamad; Alissa Nabillah; Siti Maesaroh (Jurnal Ilmiah Sains dan Teknologi, 2025)
PT XYZ needs to maintain a balance between operational efficiency and system security through theimplementation of appropriate controls, especially in USB usage and server time management. ActiveDirectory, a Windows Server feature, enables more efficient organizational security management byproviding a basic database for user and device information across the network. The Group Policyfeature in Active Directory also supports more effective management of computers and users on thenetwork, helping companies maintain the integrity, authenticity, and availability of network resources.This study aims to test the application of these technologies to improve security and data management atPT XYZ